Population density and assaults in jails for men and women - Sechrest, Dale K. (American journal of criminal justice, 1989)
Jail populations and capacities are increasing across the United States. Such increases raise questions about the potential for increased violence in crowded jails, such as those in Dade County, Florida. The study uses incident reports for the Dade County Jails Pretrial Detention Center (PTDC) for men and the Women’s Detention Center (WDC) for the year 1984. Assaults are examined in relation to total population, density by floors and total facility, and for the race/ethnicity and age of inmates. Findings show that density alone, or “crowding,” has the greatest effect on the number and rate of assaults. Neither age nor race/ethnicity appear to be significantly related to assaults, except in the WDC for white inmates. For both facilities assaults appear to decline when Black inmates are predominant in a living area and rise when whites predominate. The reasons for this phenomenon are not entirely clean.